Evaluation of Antioxidative and Neuroprotective Activities of Total Flavonoids From Sea Buckthorn (Hippophae rhamnoides L.) - Wang, Zheng; Wang, Wenqian; Zhu, Changlong; Gao, Xiangdong; Chu, Weihua (Frontiers in Nutrition, 2022)
The aim of this study was to investigate the antioxidative and neuroprotective activities of total flavonoids from sea buckthorn (Hippophae rhamnoides L.) (TFH). Results indicated that TFH possessed DPPH radicals, hydroxyl radicals and superoxide anions scavenging activities. The neuroprotective potential was assessed with acetylcholinesterase (AChE) and monoamine oxidase A (MAO-A). The inhibition rates of AChE and MAO-A by 50 μg/ml TFH were 75.85 and 51.22%, respectively. The in vivo antioxidative and neuroprotective potential of TFH were explored in Caenorhabditis elegans. In the longevity assay, TFH (50 μg/ml) significantly increased the lifespan of wild-type C. elegans (29.40%). In the hydrogen peroxide-induced oxidative stress challenge, the antioxidant capacity of TFH-treated wild-type C. elegans was significantly enhanced. The C. elegans mutant strain CL4176 was used to study the neuroprotective effect of TFH in vivo. Results showed that TFH significantly delayed paralysis in C. elegans CL4176. Our study suggested total flavonoids from sea buckthorn (Hippophae rhamnoides L.) had the potential as an antioxidative and neuroprotective agent to extend aging and treat neurodegenerative diseases.